2007
DOI: 10.1634/stemcells.2007-0429
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Nonhematopoietic Tissue Distribution by Transplanted Human Progenitor Cells with High Aldehyde Dehydrogenase Activity

Abstract: Transplanted adult progenitor cells distribute to peripheral organs and can promote endogenous cellular repair in damaged tissues. However, development of cell-based regenerative therapies has been hindered by the lack of preclinical models to efficiently assess multiple organ distribution and difficulty defining human cells with regenerative function. STEM CELLS 2008; 26:611-620 Disclosure of potential conflicts of interest is found at the end of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 60 publications
1
54
0
Order By: Relevance
“…Thus, ALDH1A1-expressing cells have a crucial role in the initiation and progression of esophageal squamous cell carcinoma. ALDH1A1 is a predominant isoform of aldehyde dehydrogenase family in mammals located in the cytoplasm 15,16 and is originally considered as a marker for normal hematopoietic progenitor cells, 17 and is also found in cancer cells with stem cell property, that is, cancer stem-like cells, in several malignant tumors including leukemia, 9 breast cancer 7 and lung cancer. 8,18 Wang et al 19 reported that ALDH1A1 was located in the nuclei of esophageal squamous cell carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ALDH1A1-expressing cells have a crucial role in the initiation and progression of esophageal squamous cell carcinoma. ALDH1A1 is a predominant isoform of aldehyde dehydrogenase family in mammals located in the cytoplasm 15,16 and is originally considered as a marker for normal hematopoietic progenitor cells, 17 and is also found in cancer cells with stem cell property, that is, cancer stem-like cells, in several malignant tumors including leukemia, 9 breast cancer 7 and lung cancer. 8,18 Wang et al 19 reported that ALDH1A1 was located in the nuclei of esophageal squamous cell carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cells derived from uncultured CB ALDHbr cells during a 2 to 3-month period after transplantation can home to several nonhematopoietic tissues in response to chronic injury caused by genetic lysosomal storage disease [43] and by CCl 4 -induced liver damage [44] in mouse xenograft models. Such dispersion of human cells to tissues was not observed in animals engrafted with ALDHlow cells.…”
Section: Other Tissue Repair Models Involving Human Cb Aldhbr Cellsmentioning
confidence: 99%
“…22 We have previously shown that human umbilical cord blood cells selected for high ALDH activity (ALDH hi ) were enriched for hematopoietic repopulating cells 23,24 and exhibited widespread distribution of nonhematopoietic (CD45 Ϫ ) cells after transplantation into the ␤-glucuronidase-deficient nonobese diabetic/severe combined immunodeficiency/mucopolysaccharidosis type VII (NOD/SCID/MPSVII) mouse. 25 Thus, nonhematopoietic cells with potentially proangiogenic functions may also possess high ALDH activity, 26 whereas cultured mature ECs with enhanced proliferative and migratory activity were previously shown to be ALDH-low. 27 Here we show that selection of human BM cells with high ALDH activity purifies a functionally heterogeneous group of hematopoietic and nonhematopoietic colony-forming cells based on a conserved progenitor cell function.…”
Section: Introductionmentioning
confidence: 99%